Nonlinear optical behavior of lanthanide phthalocyanines and their conjugates with a selection of nanomaterials - Sekhosana, Kutloano Edward (Rhodes University, Faculty of Science, Department of Chemistry, 2017)
This thesis presents novel asymmetrical and symmetrical lanthanide phthalocyanines (Pcs) characterized using a number techniques including proton nuclear magnetic resonance, electron spin resonance, time correlated single photon counting, FTIR spectrometry, MALDI-TOF mass spectrometry, UV-Vis spectrometry, Raman spectroscopy and CHNS elemental analysis. The design of theses lanthanide Pcs takes the form of mononuclear, binuclear, trinuclear, bis- and tris(phthalocyanines). Nanomaterials such as zinc oxide nanoparticles (ZnO NPs), multi-walled carbon nanotubes (MWCNTs) and graphene oxide nanosheets (GONS) (oxidized and reduced) were employed for covalent linkage to mono- and binuclear phthalocyanines as conjugates. Transmission electron microscopy was used to characterize ZnO NPs, MWCNTs and GONS alone and when linked to lanthanide Pcs. Lanthanide Pcs alone and when linked to ZnO NPs, MWCNTs and GONS where embedded in polymers such as poly (methyl methacrylate) (PMMA), poly (bisphenol A carbonate) (PBC) and poly (acrylic acid) (PAA) for thin film preparation. The thickness of the thin films was determined by utilization of the knife edge attachment of the A Bruker D8 Discover X-ray diffraction (XRD). Optical limiting properties of lanthanide Pcs alone and as conjugates in solution and when incorporated into polymers were determined by employing a Z-scan technique. It emerged that low symmetry lanthanide Pcs (19, 20 and 21), the blue forms of bis(phthalocyanines) (only in solution; 24 and 28) as well as tris(phthalocyanines) (30 and 31) exhibit low limiting threshold (Ilim) values in solution and thin films (particularly PBC and PAA). The low limiting threshold values make these lanthanide Pcs reliable optical limiters.
Keywords: Uncatalogued